Exposure to domestic violence during pregnancy: Perceptions and coping mechanisms of a vulnerable group - E Libuku; L F Small (AOSIS, 2008)
The purpose of this study was to explore and describe the perceptions of maternity clients' relating to domestic violence. A quantitative, exploratory and descriptive design was utilised. The population consisted of maternity patients admitted to a referral hospital in Windhoek, Namibia. The findings indicate that some perceptions reflect biographical differences such as education, age and economic status. In some instances, perceptions of maternity clients were in line with findings published in existing literature that reported socio-economic circumstances and familial obligations which forced women to endure abuse. It was recommended that these differences in perceptions be taken into account during the counselling of maternity clients or while health education is being given. Opsomming Die doel van hierdie studie was om swanger vroue se persepsies in verband met gesinsgeweld verkennend te beskryf. 'n Kwantitatiewe, verkennende en beskrywende ontwerp is gebruik. Die studie was ook kontekstueel in ontwerp. Die populasie het uit swanger vroue bestaan wat in 'n verwysingshospitaal in Windhoek, Namibië, opgeneem is. Daar is bevind dat sommige persepsies deur biografiese veranderlikes bepaal word soos geletterdheidsvlak, ouderdom en ekonomiese status. In sekere gevalle is gevind dat die persepsies van swanger vroue ooreenstem met bevindinge in bestaande literatuur deurdat sosio-ekonomiese omstandighede en familieverpligtinge hulle dwing om gesinsgeweld te verduur. Daar word aanbeveel dat hierdie verskillende persepsies gedurende beradingsessies met swanger vroue of tydens gesondheidsopvoeding in ag geneem word.